Filsafat Islam Sebagai Landasan Pedagogi: : Menciptakan Lingkungan Belajar Yang Inklusif Dan ‎Holistik - YAZID, MUHAMMAD (Prgram Studi Pendidikan Agama Islam, 2025)
Islamic philosophy plays a crucial role in shaping the foundation of inclusive and holistic pedagogy. Today’s education faces challenges of social complexity and cultural diversity that require new approaches. This study aims to explore how the principles of Islamic philosophy can be integrated into educational practices to create a supportive learning environment for character development and social justice. The research method employed is literature review, analyzing classical and modern texts on Islamic educational philosophy. The findings indicate that applying values such as tolerance, cooperation, and justice in the learning process can enhance relationships between educators and students while fostering a respectful learning atmosphere. The conclusion emphasizes that Islamic philosophy is not only relevant but also essential in formulating educational strategies that respond to the diverse needs of society.